A Profile of West European "Nuclear Pacifism". - United States. International Communication Agency. Office of Research.; Winn, Gregory F.T. (Tufts University. Tisch Library., 2019)
This paper reports findings from surveys in the Netherlands, West Germany, France, the United Kingdom, Italy and Norway on INF and other security issues.; Research Memorandum M-1/7/82